2012
DOI: 10.1186/1476-069x-11-23
|View full text |Cite
|
Sign up to set email alerts
|

On the estimation of heat-intensity and heat-duration effects in time series models of temperature-related mortality in Stockholm, Sweden

Abstract: BackgroundWe examine the effect of heat waves on mortality, over and above what would be predicted on the basis of temperature alone.MethodsPresent modeling approaches may not fully capture extra effects relating to heat wave duration, possibly because the mechanisms of action and the population at risk are different under more extreme conditions. Modeling such extra effects can be achieved using the commonly left-out effect-modification between the lags of temperature in distributed lag models.ResultsUsing da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 20 publications
4
43
0
1
Order By: Relevance
“…Heat wave effects were shown to amount to a stable and statistically significant 8.1-11.6% increase in excess deaths per heat wave day 27 ; in more than 40 American cities, heat wave mortality risk increased 0.38% for every 1-day increase in heat wave duration. 28 The longest heat waves were associated in Spain with daily mortality.…”
Section: Discussionmentioning
confidence: 98%
“…Heat wave effects were shown to amount to a stable and statistically significant 8.1-11.6% increase in excess deaths per heat wave day 27 ; in more than 40 American cities, heat wave mortality risk increased 0.38% for every 1-day increase in heat wave duration. 28 The longest heat waves were associated in Spain with daily mortality.…”
Section: Discussionmentioning
confidence: 98%
“…In a multicity U.S. study modeling temperature as a spline and heat wave as an indicator variable, Gasparrini and Armstrong (2011) and Barnett et al (2012) found added heat-wave effects of 0–7% in the United States, with the greatest added heat-wave effect when the temperature spline had the fewest df, as did Rocklov et al (2012) in Sweden. This finding can be explained by the fact that intensity and duration of extreme heat are correlated, so estimates of heat-wave effects diminish as the independent effects of extreme heat are allowed to be more intense in the model.…”
Section: Discussionmentioning
confidence: 99%
“…To study additional effects occurring from the duration of temperature extremes (27) (the duration of heat and cold waves) we created a cold wave and a heat wave duration variable, considering days in sequence below and above the 2nd and 98th percentile of temperature, respectively. This variable was given the value 1 on the second day of the cold or heat wave, 2 on the third and so on.…”
Section: Methodsmentioning
confidence: 99%